2006
DOI: 10.1002/adma.200600387
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Triggered Smart Drug Release from a Poly(dimethylsiloxane)– Mesoporous Silica Composite

Abstract: Ultrasound is used as an external trigger for the pulsatile release of the drug ibuprofen. The system is composed of mesoporous silica as the drug reservoir and poly(dimethylsiloxane) (PDMS) as an implantable body. This system could find use for in vivo delivery of drugs in response to changes in physiological conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
173
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(176 citation statements)
references
References 41 publications
2
173
0
1
Order By: Relevance
“…This polarity change provokes the opening of the gates of the mesoporous channels resulting in a release of drug molecules. Kim et al 159 reported a silica nanoparticle-based DDS that could be triggered by ultrasound. The system was composed of mesoporous silica as the drug reservoir and poly dimethylsiloxane (PDMS) as gatekeeper to suppress the initial fast release.…”
mentioning
confidence: 99%
“…This polarity change provokes the opening of the gates of the mesoporous channels resulting in a release of drug molecules. Kim et al 159 reported a silica nanoparticle-based DDS that could be triggered by ultrasound. The system was composed of mesoporous silica as the drug reservoir and poly dimethylsiloxane (PDMS) as gatekeeper to suppress the initial fast release.…”
mentioning
confidence: 99%
“…The loaded drugs could be subsequently released after the collapse and transformation of calcium phosphate nanocarriers to pin-shaped crystallites [14]. Another controllable, smart, pulsatile ultrasonic-triggered drug-releasing system was constructed based on the poly (dimethylsiloxane)-mesoporous silica system, which greatly suppressed the 'burst effect' of traditional mesoporous silicabased DDSs [15].…”
Section: Responsive Drug Releasing By Exogenous Triggersmentioning
confidence: 99%
“…However, development of such systems is currently heavily reliant on responsive polymeric materials [4,5] that are responsive, for example, to enzymes [6], light [7], temperature [8], calcium [9] and ultrasound [10]. Such systems usually incorporate responsive elements, e.g.…”
Section: Introductionmentioning
confidence: 99%